2016
DOI: 10.1007/s00395-016-0571-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitroglycerin induces DNA damage and vascular cell death in the setting of nitrate tolerance

Abstract: Nitroglycerin (GTN) and other organic nitrates are widely used vasodilators. Their side effects are development of nitrate tolerance and endothelial dysfunction. Given the potential of GTN to induce nitro-oxidative stress, we investigated the interaction between nitro-oxidative DNA damage and vascular dysfunction in experimental nitrate tolerance. Cultured endothelial hybridoma cells (EA.hy 926) and Wistar rats were treated with GTN (ex vivo: 10-1000 µM; in vivo: 10, 20 and 50 mg/kg/day for 3 days, s.c.). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…7 It has been reported that GTN therapy may cause nitrate tolerance through DNA damage, induction of microRNA-199, and endothelial dysfunction. [8][9][10] S-nitrosylation is a ubiquitous redox-related modification of cysteine thiol by NO, which transduces NO bioactivity. 11,12 Accumulating evidence suggests that S-nitrosylation, such as S-nitrosothiols, plays key roles in human health and diseases.…”
Section: Study Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 It has been reported that GTN therapy may cause nitrate tolerance through DNA damage, induction of microRNA-199, and endothelial dysfunction. [8][9][10] S-nitrosylation is a ubiquitous redox-related modification of cysteine thiol by NO, which transduces NO bioactivity. 11,12 Accumulating evidence suggests that S-nitrosylation, such as S-nitrosothiols, plays key roles in human health and diseases.…”
Section: Study Highlightsmentioning
confidence: 99%
“…It has been reported that GTN therapy may cause nitrate tolerance through DNA damage, induction of microRNA‐199, and endothelial dysfunction . S‐nitrosylation is a ubiquitous redox‐related modification of cysteine thiol by NO, which transduces NO bioactivity .…”
mentioning
confidence: 99%
“…The method of densitometric quantification of endothelial DHE staining was adopted from a published protocol [68](A-C) Stainings were selected from unused pictures and graphs were drafted de novo from original data published in Schuhmacher et al, Hypertension 2010 [23]. Aortic endothelial DHE staining correlated well with endothelial dysfunction measured by ACh-dependent relaxation using isometric tension recording [62] (D), impaired calcium ionophore-stimulated tolerance in rat [38], mouse [39], rabbits [40] and human [41]; isosorbide-5-mononitrate-induced endothelial dysfunction [26]; cyclooxygenase inhibitor-induced NADPH oxidase activation in rat [42]; atherosclerosis in Watanabe Heritable Hyperlipidemic (WHHL) rabbits [40,43], ApoE knockout [44] and high fat diet fed mice (Steven et al, in revision in Cardiovasc. Res.…”
Section: Dihydroethidium Oxidative Fluorescence Microtopography (Dhe mentioning
confidence: 99%
“…We employed the L-012 ECL assay for measuring mitochondrial peroxynitrite formation in nitrate tolerance induced by nitroglycerin in rats [39,[112][113][114][115][116][117] or mice [56,118,119]. In these publications L-012 ECL signals correlated well with 3-nitrotyrosine levels in mitochondria of various tissues upon in vitro and in vivo nitroglycerin treatment, with ROS and RNS detection by other assays such as HPLC-based 2-hydroxyethidium measurement or dihydrorhodamine fluorescence, inhibition of the redox-sensitive enzyme mitochondrial aldehyde dehydrogenase (ALDH-2) and other markers of oxidative stress such as products of lipid peroxidation or 8-oxo-G and was improved by various antioxidant therapies (reviewed in [120]).…”
Section: L-012-based Whole Blood Chemiluminescence Assay (L-012 Oxidamentioning
confidence: 99%
See 1 more Smart Citation